Overexpression of Populus trichocarpa CYP85A3 promotes growth and biomass production in transgenic trees. Issue 10 (17th June 2017) - Jin, Yan‐Li; Tang, Ren‐Jie; Wang, Hai‐Hai; Jiang, Chun‐Mei; Bao, Yan; Yang, Yang; Liang, Mei‐Xia; Sun, Zhen‐Cang; Kong, Fan‐Jing; Li, Bei; Zhang, Hong‐Xia
Summary: Brassinosteroids (BRs) are essential hormones that play crucial roles in plant growth, reproduction and response to abiotic and biotic stress. In Arabidopsis, AtCYP85A2 works as a bifunctional cytochrome P450 monooxygenase to catalyse the conversion of castasterone to brassinolide, a final rate‐limiting step in the BR‐biosynthetic pathway. Here, we report the functional characterizations of PtCYP85A3, one of the three AtCYP85A2 homologous genes from Populus trichocarpa . PtCYP85A3 shares the highest similarity with AtCYP85A2 and can rescue the retarded‐growth phenotype of the Arabidopsis cyp85a2‐2 and tomato d x mutants. Constitutive expression of PtCYP85A3, driven by the cauliflower mosaic virus 35S promoter, increased the endogenous BR levels and significantly promoted the growth and biomass production in both transgenic tomato and poplar. Compared to the wild type, plant height, shoot fresh weight and fruit yield increased 50%, 56% and 43%, respectively, in transgenic tomato plants. Similarly, plant height and stem diameter increased 15% and 25%, respectively, in transgenic poplar plants. Further study revealed that overexpression of PtCYP85A3 enhanced xylem formation without affecting the composition of cellulose and lignin, as well as the cell wall thickness in transgenic poplar. Our finding suggests that PtCYP85A3 could be used as a potential candidate gene for engineering fast‐growing trees with improved wood production.